Social support as a mediator in the relationship between perceived stress and nomophobia: An Investigation among Malaysian university students during the COVID-19 pandemic - Lai, Samantha Arielle; Pang, Khong Yun *; Siau, Ching Sin; Chan, Caryn Mei Hsien; Tan, Yee Kee; Ooi, Pei Boon *; Mohamad Ikhram Bin, Mohamad Ridzuan; Ho, Meng Chuan (Springer Verlag (Germany), 2023)
This study examined the mediating role of social support in the relationship between perceived stress and nomophobia among Malaysian university students during the COVID-19 pandemic. A cross-sectional study was conducted with N = 547 university students. Participants answered a self-administered questionnaire measuring nomophobia, social support, and perceived stress. Exploratory analyses were conducted using partial least square structural equation modelling. We found that perceived stress was positively associated with nomophobia during the COVID-19 pandemic, whilst social support partially mediated the relationship between perceived stress and nomophobia. The results of this study indicated that stress may be buffered by social support in individuals with higher levels of nomophobia.